Kidney transplant from deceased donors with acute kidney injury: Assesment of graft function and survival - Lima, Adriana Serpa Brandão de Andrade; Andrade, Lucas Boeckmann de; Leão, Ana Beatriz Assis Almeida Carneiro; Leão, Cristiano Souza; Cavalcanti Neto, Ruy de Lima; Cavalcante, Samuel de Alencar; Andrade, Amaro Medeiros de; Andrade, João Marcelo Medeiros de (Brazilian Journal of Transplantation, 2013)
Purpose: Organs from donors with acute renal injury (ARF) seem to be associated to good results, although it is required to check such efficiency. Methods: We made a retrospectively review of 432 kidney transplants performed at the UGT-IMIP between 11/2007 and 12/2012. According to the type of donors, we classified as standard criteria donors (SCD), expanded criteria donors (ECD), donors with acute kidney injury (AKID) and live donors (LD). We compared the creatinine clearan- ce at 3 months (CLCR3m) and 1-year (CLCR1y), the prevalence and length of delayed graft function (DGF), and the graft survival (GS) at 3 months and 1 year. Results: 432 transplants were assessed. Among these, 183 SCD, 98 ECD, 87 ARFD, and 64 LD. There was no difference on GS between groups at 3 months and 1 year. The CLRC3m was smaller than the AKID group (p=0,004), but there was no difference on the CLCR1y between groups. The prevalence of DGF was similar between groups SCD, ECD, and AKID; however, the recovery time of DGF was smaller among groups ECD and AKID (p<0,0001). Conclusions: There were no differences on the GS and graft function between groups. Organs from donors with ARF may be used attempting to increase the numbers of donors.